Beyond 'behaviour': The institutionalisation of practice and the case of energy-efficient lighting in Denmark. (August 2019) - Genus, Audley; Jensen, Charlotte
In contrast with approaches which focus on behaviour relating to purchasing decisions and attitudes of consumers, research on social practices emphasises the analysis of what people routinely do and the elements of practice underpinning institutionalisation of collective conventions. This article contributes to this growing stream of literature by investigating social practices relevant to energy-efficient lighting in Denmark. It reports on data collected from 'ethnographic interviews' conducted in 16 Danish households and suggests that drawing on insights from institutional theory could enrich our understanding of social practices, for example, in relation to the emergence and embedding of new practices and shedding of 'old' ones. In addition to highlighting the elements of practice previously identified as integral to collective conventions and connections among different domains of practice, this article recognises the importance of phenomena usually examined in work emphasising institutional analysis. It suggests that policy interventions need to recognise various kinds of institutional rules and processes which confer legitimacy to emerging practices, to facilitate their sedimentation and contribute to realising environmentally sustainable systems and societies.